The neurobiology of substance use and addiction: evidence from neuroimaging and relevance to treatment. (November 2020) - Hayes, Alexandra; Herlinger, Katherine; Paterson, Louise; Lingford-Hughes, Anne
SUMMARY: Addiction is a global health problem with a chronic relapsing nature for which there are few treatment options. In the past few decades, neuroimaging has allowed us to better understand the neurobiology of addiction. Functional neuroimaging paradigms have been developed to probe the neural circuits underlying addiction, including reward, inhibitory control, stress, emotional processing and learning/memory networks. Functional neuroimaging has also been used to provide biological support for the benefits of psychosocial and pharmacological interventions, although evidence remains limited and often inconclusive in this area, which may contribute to the variability in treatment efficacy. In this article, we discuss the changing definitions and clinical criteria that describe and classify addictive disorders. Using examples from functional neuroimaging studies we summarise the neurobiological mechanisms that underpin drug use, dependence, tolerance, withdrawal and relapse. We discuss the links between functional neuroimaging and treatment, outline clinical management in the UK and give an overview of future directions in research and addiction services.